Review of the Validity and Legal Justice of the Prosecutor's Demands in the Corruption Case Number: 2/Pid.Sus.TPK/2023/PN.Mks - Khaidir, Khaidir; Shodiq, MD; Prasetyo, Dedy Ardian (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
The validity and fairness of the law against the charges are very important to be considered by the Public Prosecutor. The prosecution process by the public prosecutor begins with the study of the investigation file, then from the results of the public prosecutor's research can identify what evidence and the evidentiary strength is fulfilled, then for the inherent weaknesses known in the case file to prepare the juridical—accurate facts to anticipate problems that arise in the effort to prove in court. The problem in this paper is the basis for the Public Prosecutor's consideration regarding the Corruption Crime case and how to review the aspects of legality and legal justice against the Public Prosecutor's demands in case Number: 2/Pid.Sus.TPK/2023/PN.Mks. This paper uses a type of normative juridical method with the consideration that the problem being studied is relevant to the regulations and how to handle it in judicial practice. From the results of the research carried out, it can be concluded as follows: first, the Public Prosecutor in his Indictment in the form of an "alternative indictment" has been read out in the trial on January 13, 2023, filing an indictment against the defendant Eltinus Omaleng with the First Indictment Article 2 paragraph (1) Jo Article 18 of Law No. 31 of 1999 concerning the Eradication of Corruption Crimes Jo Article 55 paragraph (1) 1 of the Criminal Code Jo Article 64 (1) of the Criminal Code and the Second Indictment of Article 3 Jo Article 18 of Law No. 31 of 1999 concerning the Eradication of Corruption Jo Article 55 paragraph (1) 1 of the Criminal Code Jo Article 64 (1) of the Criminal Code. Second, the indictment and demands of the Public Prosecutor in case Number: 2/Pid.Sus.TPK/2023/PN.Mks do not have legal validity and justice, because all elements of the articles charged were not proven at trial.